2019
DOI: 10.1152/ajpheart.00045.2019
|View full text |Cite
|
Sign up to set email alerts
|

Advanced maternal age and the impact on maternal and offspring cardiovascular health

Abstract: Delaying pregnancy, which is on the rise, may increase the risk of cardiovascular disease in both women and their children. The physiological mechanisms that lead to these effects are not fully understood but may involve inadequate adaptations of the maternal cardiovascular system to pregnancy. Indeed, there is abundant evidence in the literature that a fetus developing in a suboptimal in utero environment (such as in pregnancies complicated by fetal growth restriction, preterm birth, and/or preeclampsia) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 79 publications
5
55
0
3
Order By: Relevance
“…Regarding sociodemographic features, women with unfulfilled reproductive desires were younger than women with fulfilled reproductive desires. The possibility of completing reproductive desires increases over the years [ 42 ], so an age difference between the two groups had been expected. The proportion of women with completed mandatory education level was higher in women with unfulfilled reproductive desires.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sociodemographic features, women with unfulfilled reproductive desires were younger than women with fulfilled reproductive desires. The possibility of completing reproductive desires increases over the years [ 42 ], so an age difference between the two groups had been expected. The proportion of women with completed mandatory education level was higher in women with unfulfilled reproductive desires.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age at delivery, 24 maternal smoking status during the first 3 months of pregnancy, [25][26][27] maternal socioeconomic status (SES), paternal SES, maternal highest education attainment, and paternal highest education attainment 11,[28][29][30] were identified as possible confounders ( Figure 1) and adjusted for in all analyses. The above variables were chosen based on previous literature and availability in present dataset.…”
Section: Descriptive and Confounding Variablesmentioning
confidence: 99%
“…While previous studies have demonstrated the association of PE development in pregnant women and future cardiovascular complications such as the development of hypertension, diabetes, ischemic disease, and other cardiovascular diseases, recent literature has suggested the need for additional studies for a more complete understanding of how this relationship is established (7)(8)(9)(10)(11).…”
Section: ' Introductionmentioning
confidence: 99%